Theology, creation, and environmental ethics: from creatio ex nihilo to terra nullius - Bauman, Whitney (Routledge studies in religion, 2009)
Winner of the John Templeton Award for Theological Promise, 2009. This book argues that the Christian doctrine of creatio ex nihilo sets up a support system for a "logic of domination" over others. It follows a genealogical method in examining how the concept of creation out of nothing materializes in the world throughout different periods in the history of the Christian West